Training zones through muscle oxygen saturation a graded exercise test in cyclists and triathletes - Vasquez Bonilla, A. A.; González-Custodio, A.; Timón, R.; Camacho-Cardenosa, A.; Camacho-Cardenosa, M.; Olcina, G. (Biology of Sport, 2023)
Use of muscle oxygen saturation (SmO2) has been validated as a performance factor during incremental exercise with portable near-infrared stereoscopy (NIRS) technology. However, there is little knowledge about the use of SmO2 to identify training zones. The objective of this study was to evaluate the metabolic zones by SmO2: maximum lipid oxidation zone (Fatmax), ventilatory thresholds (VT1 and VT2) and maximum aerobic power (MAP) during a graded exercise test (GXT). Forty trained cyclists and triathletes performed a GXT. Output power (W), heart rate (HR), oxygen consumption (VO2), energy expenditure (kcal/min) and SmO2 were measured. Data were analysed using the ANOVA test, ROC curves and multiple linear regressions. Significance was established at p = 0.05. SmO2 decreases were observed from baseline (LB) to Fatmax (? = -16% p < 0.05), Fatmax to VT1 (? = -16% p < 0.05) and VT1 to VT2 (? = -45% p < 0.01). Furthermore, SmO2 together with weight, HR and output power have the ability to predict VO2 and energy expenditure by 89% and 90%, respectively. We conclude that VO2 and energy expenditure values can be approximated using SmO2 together with other physiological parameters and SmO2 measurements can be a complementary parameter to discriminate aerobic workload and anaerobic workload in athletes.